Variable Determinants of Inflation Rate: A Study of BI Data Analysis 2021-2023 - Melati, Yasinta; Setyowati, Eny (Universitas Negeri Semarang, 2024)
This research aims to analyze the influence of e-money transaction value, e-money transaction volume, money supply and exchange rate on the inflation rate in Indonesia. The data used in this research is secondary data obtained from Bank Indonesia (BI) and the Central Statistics Agency (BPS), with a time span from 2021 to 2023. This research uses a quantitative approach and applies classic assumption tests for data analysis. The results of this research show that the value of e-money transactions, the volume of e-money transactions, and the exchange rate are proven to have an influence on inflation, while the amount of money in circulation does not show a significant influence on inflation. It was found that the value of e-money transactions had a positive and significant influence on inflation, while the volume of e-money transactions had a negative and significant influence on inflation. On the other hand, the money supply does not have a significant effect on inflation, while the exchange rate shows a positive and significant effect on inflation. From this research it can be concluded that e-money has a different influence on inflation depending on the variables measured: the value of e-money transactions contributes positively to inflation, while the volume of e-money transactions contributes negatively to inflation.